Satisfaction as a mediator between perceptions of service quality and loyalty related to the Indonesian Social Security Mobile app - Balqiah, Tengku Ezni; Nilakurnia, Roswita; Astuti, Rifelly Dewi; Wulandari, Permata; Supriadi, Arief Dahyan; Saragih, Tarimantan Sanberto; Augustin, Eldest; Pradana, Fadly Eka; Mahaganti, Fergie S; Pramasanti, An Nisa; Hutabarat, Rendra Hymne Fajar (UI Scholars Hub, 2025)
Manuscript type: Research Article Research Aims: to determine whether the perceived service quality factors could promote user Jamsostek Mobile (JMO) satisfy and continue to use JMO Design/methodology/approach: Data was gathered through an online survey of JMO users to analyse three hypotheses using Structural Equation Modelling (SEM) method with SmartPLS Research Findings: the result demonstrated that all hypotheses are supported that indicate there are three dimension of JMO attributes could develop Perceived Service Quality. Moreover, this variable could enhance loyalty through satisfaction. Theoretical Contribution/Originality: Using the Stimulus–Organism–Response (S-O-R) Model, this study develop framework to strengthen the explanation of the sequential relationship between stimulus, organism, and response toward mobile apps, in the context of social security insurance. Practitioner/Policy Implication: As the highest contributors, company could increase user perception in service and function by enhancing authenticity, interactivity, and understandability toward Jamsostek Mobile (JMO). Research limitation/Implications: User response depends on their ability to remember the previous experience, do not consider the user app frequency, and do not focus on specific service of insurance that could deliver different impacts on responses. Future studies should consider to conducted an exploratory to identify measurement of JMO attributes. Moreover. consider enjoyment, and risk as organisms.